PENERAPAN MODEL ERROR CORRECTION MECHANISM: DETERMINAN PRODUKSI KOPI DI INDONESIA PERIODE 2002-2018 - Zasya Safitri; Lia Yuliana (Politeknik Statistika STIS, 2020)
Coffee is one of the estate commodities that has an important role in economic activities in Indonesia. However, the condition of coffee production in Indonesia fluctuates. Meanwhile, the condition of the domestic coffee market is still quite large with probabilities for coffee as an increasingly open export commodity. In the long-term, it is feared that coffee production cannot fulfill the domestic and international markets. The purpose of this study is to determine the factors that influence the long-term and short-term coffee production in Indonesia as a determinant of the right policy to increase production. The method used in this study is Error Correction Mechanism (ECM) with the study period starting from 2002 to 2018. From the results of the discussion, in the long-term the mature area variable and the domestic coffee price significantly influence coffee production, while the number of coffee farmers did not significantly influence coffee production. Furthermore, in the short-term only the number of coffee farmers variable which significantly influence coffee production, while the mature area and domestic coffee price variable did not significantly influence coffee production.